EFEKTIFITAS PENDISTRIBUSIAN ZAKAT PADA PROGRAM PADANG SEJAHTERA STUDI KASUS: BAZNAS KOTA PADANG - Deni Wahyuni, Elni Sumiarti (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
Zakat is a mahdah worship related to property. In addition, zakat is also one of theembodiment of social awareness in community life that can be used as an instrument to reducepoverty. To achieve zakat implementation properly and optimally, it is necessary to havepower and government intervention.Initially zakat implementation in Indonesia is limited to individuals, but since 1990 themanagement of zakat began to be directed in the form of institutions in the form of Amil ZakatAgency as mandated by Law No. 38 of 1999 on the Management of Zakat. The spirit anddesire of the establishment of zakat as an Islamic financial instrument that can be empoweredto reduce poverty also become the spirit and desire of the government and Muslims in PadangCity by establishing the Amil Zakat Agency of Padang City. Total Population of Padang City:1,000,000 inhabitants = 232,000 family, BAPPEDA Data (2014) Padang City has 32,000 poorfamily.The distribution of zakat funds already has rules in Al-Qur'an At-Taubah: 60 is on theeight asnaf (8), so Baznas Kota Padang applies in six (6) programs namely Padang Religius,Padang Sejatera, Padang Sehat, Padang cerdas, Padang makmur and caring Padang.Distribution is done evenly but still proportional to the number of poor per-district in PadangCity, with the aim Mustahiq become Muzaqi.Keywords:Zakat, Asnaf, Muzaki and Mustahiq